To find the efficacy of crude extract from plants on germination of seeds - Ravi Kumar Patil; Chetan DM; Abhilash K B; Raghupathi Achari (International Journal of Phytomedicine, 2018)
Germination is the growth of an embryonic plant contained within a seed; it results in the formation of the seedling. The seed of a higher plant is a small package produced in a fruit or cone after the union of male and female sex cells. All fully developed seeds contain an embryo and, in most plant species some store of food reserves, wrapped in a seed coat. Some plants produce varying numbers of seeds that lack embryos, these are called empty seeds, and never germinate. Most seeds go through a period of quiescence where there is no active growth; during this time the seed can be safely transported to a new location and/or survive adverse climate conditions until circumstances are favorable for growth. Quiescent seeds are ripe seeds that do not germinate because they are subject to external environmental conditions that prevent the initiation of metabolic processes and cell growth. Under favorable conditions, the seed begins to germinate and the embryonic tissues resume growth. In the present study, research was done to find the effect of crude extract of plants on germination of seeds. The plants which we have chosen may show the positive or negative effect on the germination of seeds. This has some importance in the rain fed areas. Even the specific plant extract soaked and sow in land may helpful to tolerate the drought conditions. Also study is helpful to agriculture or agricultural industry. It helps to find out the anti sprouting property of the plants. However, further work is needed to improve this method.